Preparation of Black Phosphorus and the Application in Biomedicine - Qian, Kawai (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This work presents an in-depth exploration of black phosphorus (BP) nanosheets, highlighting their transformative potential in advancing cancer treatment. As cancer continues to be a leading cause of death worldwide, current therapies often fall short of delivering targeted and effective treatment with minimal side effects. In response to this need, BP nanosheets are considered to be a kind of promising multifunctional materials for cancer therapy. The work begins with an overview of the pressing challenges and the limitations of current targeted therapies, including issues like drug resistance and systemic toxicity. It then delves into the various methods of BP nanosheet preparation, including top-down and bottom-up approaches, which are critical in enhancing their properties for biomedical applications. Furthermore, the diverse applications of BP nanosheets are thoroughly examined, particularly their roles in photothermal therapy, photodynamic therapy, and drug delivery. BP nanosheets also offer the capability to regulate the tumour microenvironment and enable combined treatment modalities. Their multifunctionality and potential to integrate multiple therapeutic approaches provide a compelling solution to overcome the drawbacks of existing cancer treatments, thus paving the way for safer and more effective therapies.